Aplikasi Transliterasi Notasi Balok Menjadi Notasi Angka Menggunakan Format MusicXML - Dimpudus, Jessy Katharina Lucia; Sambul, Alwin M.; Lumenta, Arie S.M. (Universitas Sam Ratulangi, 2022)
A choir is an ensemble consisting of a group of singers led by a conductor. Partitur is a songwriting text that is often used in choirs to learn a song. International standard songwriting is block notation, not number notation. Most of people who have just joined the choir are more accustomed to using scores that are notated by numbers rather than scores that are notated by blocks so that during the process of practicing and learning songs that are notated with blocks, those who do not understand about notation of blocks will have difficulty in learning songs that are notated with blocks. The research entitled